PRESENCE AND LEVELS OF CONCENTRATION OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHS) IN SMOKED FISH, HIDES AND SKIN OF SLAUGHTER CATTLE AND GOATS IN AWKA URBAN, NIGERIA - OFOMATA, IKECHUKWU; OBODOECHI, LYNDA ONYINYE; OBIDIKE, REGINALD IKECHUKWU; NWANTA, JOHN ANAELOM (International Journal of Current Pharmaceutical Research, 2019)
Objective: This study evaluated the presence and concentration of PAHs in singed and unsinged hides and skin of slaughter cattle and goats and smoked and non-smoked fish in Awka urban area of Anambra State, Nigeria. Methods: Sixty samples of singed and unsinged hides and skin for were collected from Kwata slaughterhouse in Awka town where fish tissues were also collected from fish smoking spots in Awka urban. The samples were examined for the presence PAHs such as: benzo[a]pyrene; benzo[a]anthracene; benzo[k]flouranthene and indeno[1-2-3cd]pyrene using gas chromatography equipped with flame ionization detector. Results: The result showed that the mean concentrations (µg/kg) of benzo[a]pyrene and indeno [1-2-3cd]pyrene in unsinged cattle hides were 7.89±7.77 and 2.25±0.97 respectively. The mean concentrations upon singeing were of 15.81±14.93 and 3.55±2.89. The mean concentrations (µg/kg) of benzo[a]pyrene; benzo[k]flouranthene and indeno[1-2-3cd]pyrene in unsigned goat skins were 6.52±10.77; 6.58±5.93 and 3.48±0.00 respectively. When the goatskin was singed, the mean concentrations were 17.50±26.03; 10.84±11.19 and 8.79±11.77. The mean concentrations (µg/kg) of benzo[a]pyrene; benzo[k]flouranthene and indeno[1-2-3cd]pyrene in non-smoked fish were 8.65±9.67; 2.11±2.10 and 54.76±60.35 respectively. When the fish were smoked, the mean concentrations of 26.42±40.21; 6.64±11.11 and 599.36±1395.61 were recorded respectively. In all species of animals sampled, no trace of benzo[a]anthracene was detected. Conclusion: The mean concentrations of all carcinogenic PAHs detected in this work were below the maximum permissible level set by World Health Organization (WHO) and European Commission (30µg/kg) with the exception of indeno[1-2-3cd]pyrene in smoked and non-smoked fish, which was far above the permissible level.